Trafficking of phagocytic peritoneal cells in hypoinsulinemic-hyperglycemic mice with systemic candidiasis - Fraga-Silva, Thais Fernanda de Campos [UNESP]; Venturini, James [UNESP]; Arruda, Maria Sueli Parreira de [UNESP] (Springer Nature, 2013)
Background: Candidemia is a severe fungal infection that primarily affects hospitalized and/or immunocompromised patients. Mononuclear phagocytes have been recognized as pivotal immune cells which act in the recognition of pathogens, phagocytosis, inflammation, polarization of adaptive immune response and tissue repair. Experimental studies have showed that the systemic candidiasis could be controlled by activated peritoneal macrophages. However, the mechanism to explain how these cells act in distant tissue during a systemic fungal infection is still to be elucidated. In the present study we investigate the in vivo trafficking of phagocytic peritoneal cells into infected organs in hypoinsulinemic-hyperglycemic (HH) mice with systemic candidiasis. Methods: The red fluorescent vital dye PKH-26 PCL was injected into the peritoneal cavity of Swiss mice 24 hours before the intravenous inoculation with Candida albicans. After 24 and 48 hours and 7 days of infection, samples of the spleen, liver, kidneys, brain and lungs were submitted to the microbiological evaluation as well as to phagocytic peritoneal cell trafficking analyses by fluorescence microscopy. Results: In the present study, PKH+ cells were observed in the peritoneum, kidney, spleen and liver samples from all groups. In infected mice, we also found PKH+ cells in the lung and brain. The HH condition did not affect this process. Conclusions: In the present study we have observed that peritoneal phagocytes migrate to tissues infected by C. albicans and the HH condition did not interfere in this process. © 2013 Fraga-Silva et al.; licensee BioMed Central Ltd.
Keywords: animal cell; animal experiment; animal model; animal tissue; brain; Candida albicans; candidiasis; cell migration; cell phagocytosis; controlled study; fluorescence microscopy; hyperglycemia; hypoinsulinemia; inoculation; kidney; liver; lung; male; microbiological examination; mouse; nonhuman; peritoneum cell; phagocyte; spleen; Animal Structures; Animals; Candidiasis; Macrophages, Peritoneal; Male; Mice; Mice, Inbred C57BL; Mice, Obese